Repetitive impact test near uncoated and coated cutting edges for assessing their fatigue behavior. (January 2015) - Bouzakis, K.-D.; Batsiolas, M.; Skordaris, G.; Stergioudi, F.; Michailidis, N.
Abstract: The fatigue strength of the cutting edge affects dominantly the tool life, especially in the interrupted material removal processes. The cutting edge fatigue of uncoated and coated tools can be effectively assessed by the repetitive impact test. Cemented carbide inserts of various grain size, surface roughness, coating and heat treatment were investigated by applying repetitive impacts close to the cutting edge for detecting its fatigue strength. Complementary FEM simulations of the impact test, at various distances from the cutting edge, provided insights on the developed stress fields. The impact distance from the cutting edge was corroborated to have a dominant effect on the tool life, while a reduction of the roughness and the application of finer substrate grains led to an increase of the cutting edge fatigue strength. The proposed methodology facilitates an effective quality control of both coated and uncoated cutting inserts at loading conditions resembling those of interrupted cutting.